Tuberculosis incidence and risk factors among patients living with HIV/AIDS in public health service institutions in Brasilia, Federal District Incidência e fatores de risco para tuberculose em pacientes vivendo com HIV/AIDS atendidos nos serviços públicos de saúde em Brasília, Distrito Federal - Leonor Henriette de Lannoy; Juan José Cortez-Escalante; Maria do Socorro Nantua Evangelista; Gustavo Adolfo Sierra Romero (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
In order to estimate the incidence of and risk factors for developing tuberculosis, the clinical charts of a retrospective cohort of 281 HIV-positive adults, who were notified to the AIDS Program of the Health Department of Brasilia in 1998, were reviewed in 2003. All the patients were treatment-naive regarding antiretroviral therapy at the time of inclusion in the cohort. Twenty-nine patients were identified as having tuberculosis at the start of the study. Thirteen incident tuberculosis cases were identified during the 60 months of follow-up, with an incidence density rate of 1.24/100 person-years. Tuberculosis incidence was highest among patients with baseline CD4+ T-lymphocyte counts < 200 cells/µl who were not using antiretroviral therapy (incidence = 5.47; 95% CI = 2.73 to 10.94). Multivariate analysis showed that baseline CD4+ T-lymphocyte counts < 200 cells/µl (adjusted hazard ratio [AHR] = 5.09; 95% CI = 1.27 to 20.37; p = 0.02) and non-use of antiretroviral therapy (AHR = 12.17; 95% CI = 2.6 to 56.90; p = 0.001) were independently associated with increased risk of tuberculosis. Para estimar a incidência e os fatores de risco para desenvolver tuberculose foram revisados em 2003 os < prontuários de uma coorte retrospectiva de 281 adultos infectados pelo HIV que foram notificados ao Programa de Aids da Secretaria de Saúde de Brasília em 1998. Todos os pacientes eram virgens de tratamento anti-retroviral no momento da inclusão na coorte. Vinte e nove pacientes foram identificados com tuberculose na avaliação basal. Treze casos incidentes de tuberculose foram identificados durante os 60 meses de seguimento com densidade de incidência de 1,24/100 pessoas-ano. A incidência de tuberculose foi maior em pacientes com contagens basal de linfócitos T CD4+ < 200 células/µl que não se encontravam em uso de terapia anti-retroviral 5,47 (IC95%=2,73 a 10,94). A análise multivariada demonstrou que a contagem basal de linfócitos T CD4+ < 200 células/µl (adjusted hazard ratio [AHR] =5,09; IC95%=1,27 to 20,37; p =0,02) e o não uso de terapia anti-retroviral (AHR=12,17; IC95%=2,6 to 56,90; p=0,001) estiveram independentemente associados a um risco maior de tuberculose.